Effects of Bang® Keto Coffee Energy Drink on Metabolism and Exercise Performance in Resistance-Trained Adults: A Randomized, Double-blind, Placebo-controlled, Crossover Study. Issue 1 (24th August 2020) - Harty, Patrick S.; Stratton, Matthew T.; Escalante, Guillermo; Rodriguez, Christian; Dellinger, Jacob R.; Williams, Abegale D.; White, Sarah J.; Smith, Robert W.; Johnson, Baylor A.; Sanders, Mark B.; Tinsley, Grant M.
Abstract: Background: Energy drinks are often consumed by the general population, as well as by active individuals seeking to enhance exercise performance and augment training adaptations. However, limited information is available regarding the efficacy of these products. Thus, the purpose of this study was to determine the effects of a commercially available caffeine- and protein-containing energy drink on metabolism and muscular performance. Methods: Sixteen resistance-trained males ( n  = 8; mean ± SD; age: 22.4 ± 4.9 years; body mass: 78.8 ± 14.0 kg; body fat: 15.3 ± 6.4%) and females ( n  = 8; age: 24.5 ± 4.8 years; body mass: 67.5 ± 11.9 kg; body fat: 26.6 ± 7.1%) participated in this randomized, double-blind, placebo-controlled, crossover study. Following a familiarization visit, participants completed two identical visits to the laboratory separated by 5–10 days, each of which consisted of indirect calorimetry energy expenditure (EE) assessments before and after consumption of the beverage (Bang® Keto Coffee; 130 kcal, 300 mg caffeine, 20 g protein) or placebo (30 kcal, 11 mg caffeine, 1 g protein) as well as after exercise testing. In addition, participants' subjective feelings of energy, fatigue, and focus as well as muscular performance (leg press one-repetition maximum and repetitions to fatigue, maximal isometric and isokinetic squat testing) were assessed. Multiple repeated measures ANOVAs with Tukey post-hoc tests were used to analyze data. Estimates of effect size were quantified via partial eta squared (ηP 2 ) and Hedge's g. Results: A significant interaction effect was identified for EE ( p  < 0.001, ηP 2  = 0.52) but not respiratory exchange ratio ( p  = 0.17, ηP 2  = 0.11). Following consumption of the beverage, EE was 0.77 kcal·min − 1 greater than placebo at the post-beverage time point ( p  < 0.001) and 0.37 kcal·min − 1 greater than placebo at the post-exercise time point ( p  = 0.011). However, no between-condition differences were detected for any subjective or muscular performance outcomes. Conclusions: The results of this study suggest that consumption of the energy drink had minimal effects on lower-body muscular performance and subjective factors in the context of a laboratory setting. However, the beverage was found to significantly increase energy expenditure compared to placebo immediately following ingestion as well as during the recovery period after an exercise bout, suggesting that active individuals may improve acute metabolic outcomes via consumption of a caffeine- and protein-containing energy drink. Trial registration: This trial was prospectively registered at ClinicalTrials.gov (Identifier: NCT04180787 ; Registered 29 November 2019).